Angioleiomyoma of the elbow - X Pavard; B Dallaudière; P Omoumi; F.E Lecouvet; C Cyteval; B Vande berg; A Larbi (Journal of the Belgian Society of Radiology, 2014)
A 35-year-old patient was referred for ultrasound assessment of a non-painful tumor under the skin of the posterior surface of the elbow. Ultrasonography shows a well-circumscribed mass located in the fatty tissue under the skin in contact with the medial portion of the triceps tendon (Fig. A), with arterial signal on color Doppler (Fig. B). MRI report shows a well-circumscribed relatively homogeneous mass against the triceps tendon, with high signal intensity on T2-weighted sequences and some areas of low signal intensity corresponding either to fibrous tissue or vascular flow. On T1-weighted sequence, the mass appears hypointense or isointense homogeneously and clearly enhances with a Gadolinium contrast agent (Fig. C). An ultrasound guided biopsy is performed: pathological examination showed morphological and immunophenotypic aspects in favor of a vascular leiomyoma or angioleiomyoma with no criteria of malignancy. Complete excision of the lesion was performed without any complication.